IMPROVING SOCIAL STUDIES LEARNING OUTCOMES USING PROBLEM BASED LEARNING MODEL IN CLASS IV SD INPRES 3 LOLU - Misnah Misnah; Prasetyo Ignatius Kristiyadi; Herlina Herlina (Universitas Tadulako, 2020)
The purpose of this study was to improve student learning outcomes in social studies learning by using problem based learning models in class IV SD inpres 3 Lolu. The design of this study is classroom action research (CAR). The study was conducted in two cycles consisting of 4 stages: (1) Planning, (2) Acting, (3) Observation, (4) Reflection. The type of data obtained in this study are qualitative and quantitative data. The use of this model is because the plot used is quite simple and easy to implement. Data collection is done in 2 ways, namely: 1) Test to find out the improvement of student learning outcomes after the application of the PBL Model given at the end of each action (cycle). 2) Observation technique, carried out during learning activities. Analysis of several assessments used in this study, it can be concluded that: the application of problem based learning methods can improve student learning outcomes. This is in accordance with the results of the study obtained in the first cycle the observation results of the first cycle students obtained 64.28%, the observations of the teacher's activities obtained 65.62%, classical learning completeness by 25%, classical absorption 57.25%, and average learning outcomes 5.7. In the second cycle the results obtained were even better than the first cycle, namely the percentage of observation of student activities obtained 85.7%, the results of observations of teachers' activities 87.5%, the percentage of classical completeness 80%, the clapability absorbed reached 74.25% and the average learning outcomes are 7.4.